2013
DOI: 10.1158/1078-0432.ccr-12-3661
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Cancer: Revaluation of the Hygiene Hypothesis

Abstract: Several studies have shown that persistent infections and inflammation can favor carcinogenesis. At the same time, certain types of pathogens and antitumor immune responses can decrease the risk of tumorigenesis or lead to cancer regression. Infectious agents and their products can orchestrate a wide range of host immune responses, through which they may positively or negatively modulate cancer development and/or progression. The factors that direct this dichotomous influence of infection-mediated immunity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 99 publications
(116 reference statements)
1
54
0
4
Order By: Relevance
“…Endothelial VCAM-1 functions by regulating leukocyte attachment and extravasation at sites of inflammation, a process that is similar to invasion of OC cells through the mesothelium 28. Inflammatory markers (CRP and WBC) were elevated in our population, providing confirmatory evidence of a connection between the inflammation process and carcinogenesis 19,29,30. The results of our study showed no correlation between sVCAM-1 and inflammatory markers, so an influence of systemic inflammation on increased sVCAM-1 can be excluded.…”
Section: Discussionsupporting
confidence: 64%
“…Endothelial VCAM-1 functions by regulating leukocyte attachment and extravasation at sites of inflammation, a process that is similar to invasion of OC cells through the mesothelium 28. Inflammatory markers (CRP and WBC) were elevated in our population, providing confirmatory evidence of a connection between the inflammation process and carcinogenesis 19,29,30. The results of our study showed no correlation between sVCAM-1 and inflammatory markers, so an influence of systemic inflammation on increased sVCAM-1 can be excluded.…”
Section: Discussionsupporting
confidence: 64%
“…According to previous researches, some parasites have capability of antitumor activities (Darani and Yousefi 2012;Kim et al 2007;López et al 2010;Oikonomopoulou et al 2013;Pidherney et al 1993;Plumelle et al 1997) and so parasite antigens have been considered as possible targets for cancer immunotherapy (Darani and Yousefi 2012). In a retrospective study with a large population it has been shown that the prevalence of hydatid cysts in patients with cancer was significantly lower than the control group (Akgül et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that persistent infections of bacteria can initiate many cancers [1][2][3]. One class of bacteria that has attracted increasing attention from oncologists is mycoplasmas.…”
Section: Introductionmentioning
confidence: 99%